Three-Dimensional Navigated Lateral Lumbar Interbody Fusion: 2-Dimensional Operative Video. Issue 1 (12th October 2020) - Strong, Michael J; Khalsa, Siri Sahib S; Yee, Timothy J; Saadeh, Yamaan S; Smith, Brandon W; Swong, Kevin; Park, Paul
Abstract: Spondylolisthesis is a common cause of lower back and leg pain in adults. The initial treatment for patients is typically nonoperative in nature. However, when patients fail conservative management and their back and/or leg pain is recalcitrant, surgical intervention is warranted. Spinal decompression, either directly or indirectly, as well as fusion is often considered at this point. There are numerous approaches to fuse the spine, including anterior, lateral, or posterior, each with their own advantages and disadvantages.   This video illustrates a case of symptomatic spondylolisthesis occurring after laminectomy treated by lateral lumbar interbody fusion for indirect decompression and stabilization. The approach utilizes 3-dimensional navigation rather than traditional fluoroscopy, resulting in markedly decreased radiation exposure for the surgeon and staff while maintaining accuracy. Appropriate patient consent was obtained. This video demonstrates the technique for a lateral lumbar interbody fusion using navigation assistance, which is a minimally invasive technique for the treatment of spondylolisthesis.